Human Trafficking Risk Perception of Parents of Children with Autism in Nigeria - Elizabeth N. , Ebizie; Sunday Otu, Mkpoikanke; Obiageli C. , Njoku; Charles A. , Oraelosi (International Journal of Psychosocial Rehabilitation, 2021)
Given increasing challenges faced by parents of children with autism. It is imperative to investigate what might be the perception of such parents on human trafficking. Therefore, the objective of this study was to ascertain the human trafficking risk of parents with autism in Nigeria. The design the study adopted was a descriptive survey design. 40 autism parents were selected from Nsukka Local Government Area of Enugu State Nigeria participated in this study. The instrument used for data collection was HTRPQ developed by the researchers. The instrument was administered to the participates at the Special Education Centre in Nsukka LGA. The data collected were analyzed using mean and standard deviation. The result obtained showed that parents had high human trafficking risk perception. Gender differences were observed. Based on the findings, the researchers concluded that all stakeholders, education planners, childhood educators, teachers, governments, and other agencies are urgently called to strategically design implementable policies, programs, and activities that will rescue the current autistic children victims of human trafficking and also protect this category of children from falling prey into the hands of the traffickers.